The Influence of External CFRP String Reinforcement on The Behavior of Flexural RC Elements - Junaedi Utomo; Nauval Rabbani; Sri Tudjono; Ay Lie Han; Sukamta (Journal of Geoscience, Engineering, Environment, and Technology, 2021)
External reinforcement is an excellent method for improving the load carrying capacity and ductility behaviour of reinforced concrete members in flexure. Enhancement becomes a necessity when current standards mandate a higher performance compared to older codes. External reinforcement is an environmentally friendly and sustainable solution, since demolition and re-building could be postponed, and the building can be used while work in conducted on the members. Carbon Fiber Reinforced Polymers (CFRP), having a low weight-to-volume ratio and an excellent resistance to corrosion, can be used as external reinforcement to effectively increase the flexural and shear strength of a member. To evaluate the effectiveness of CFRP strings, two types of reinforced concrete T-beams were tested. The specimens consist of a strengthened member in both shear and flexure using CFRP wraps and CFRP strings, and a conventional reinforced concrete beam. The specimens were subjected to a one-point-loading system to simulate high shear stresses in combination with a maximum bending moment at mid-point. The installation of CFRP strings was conducted using the Near Surface Mounted (NSM) method, while the sheets were Externally Bonded Reinforcement (EBR). The strings and sheets were impregnated and pultruded on side. The test results showed that the strings and wraps substantially increased the ultimate load carrying capacity and ductility of the member. The ultimate load enhancement was found to be 32% from 117kN to 154kN, and the vertical deformation improved 25% from 16 mm to 20 mm. The failure mode was characterized by initial debonding of the strings in the interface between the strings and the epoxy, followed by string-rupture. The two strings ruptured concurrently, due to stress re-distribution within the member.